Introduction to human physiology - Sherwood, Lauralee (Australia Brooks/Cole, Cengage Learning, 2013)
Organized around the central theme of homeostasis - how the body meets changing demands while maintaining the internal constancy necessary for all cells and organs to function - this title helps you understand how each component of the course depends on the others and appreciate the integrated functioning of the human body.
Table of contents: Chapter 1: Introduction to physiology and homeostasis -- Chapter 2: Cell physiology -- Chapter 3 -- The plasma membrane and membrane potential -- Chapter 4: Principles of neural and hormonal communication -- Chapter 5: The central nervous system -- Chapter 6: The peripheral nervous system: afferent division, special senses -- Chapter 7: The peripheral nervous system: efferent division -- Chapter 8: Muscle physiology -- Chapter 9: Cardiac physiology -- Chapter 10: The blood vessels and blood pressure -- Chapter 11: The blood -- Chapter 12: Body defenses -- Chapter 13: The respiratory system -- Chapter 14: The urinary system -- Chapter 15: Fluid and acid-base balance -- Chapter 16: The digestive system -- Chapter 17: Energy balance and temperature regulation -- Chapter 18: Principles of endocrinology; the central endocrine glands -- Chapter 19: The peripheral endocrine glands -- Chapter 20: The reproductive system.
Includes index.
Keywords: Human physiology